(untitled) (KULT_online, 2014)
Gerhard Neumann’s most recent book on the writings of Franz Kafka examines the complex constellation of power, language, and identity. According to Neumann, Kafka’s texts quote the rituals of 19th-century society and art only to deconstruct them and thus reveal their traumatic underpinnings. While Kafka’s stories reject any claim to truthfulness, Neumann’s volume, comprising essays originally published between 1990 and 2009, will undoubtedly serve as an immovable signpost in the labyrinth that the field of Kafka studies has become.